Aldosterone and the Heart: Still an Unresolved Issue? - Catena, Cristiana; Colussi, GianLuca; Nait, Francesca; Martinis, Flavia; Pezzutto, Francesca; Sechi, Leonardo A. (Frontiers in Endocrinology, 2014)
Receptors for mineralocorticoid hormones are expressed in myocardial cells and evidence obtained in animal studies suggests that activation of these receptors causes cardiac damage independent from blood pressure levels. In the last years, many of the issues related to the effects of aldosterone on the heart have received convincing answers and clinical investigation has focused on a variety of conditions including systolic and diastolic heart failure, arrhythmia, primary hypertension, and primary aldosteronism. Some issues, however, await clarification in order to obtain better understanding of what could be the role of aldosterone blockade in prevention and treatment of cardiovascular diseases. In this article, we overview the most recent findings of animal studies that have examined the contribution of aldosterone to cardiac function and clinical studies that have investigated the influence of aldosterone on left ventricular structure and function in the setting of primary hypertension and primary aldosteronism.